2017
DOI: 10.1371/journal.pone.0180208
|View full text |Cite
|
Sign up to set email alerts
|

Prebiotic selection for motifs in a model of template-free elongation of polymers within compartments

Abstract: The transition from prelife where self-replication does not occur, to life which exhibits self-replication and evolution, has been a subject of interest for many decades. Membranes, forming compartments, seem to be a critical component of this transition as they provide several concurrent benefits. They maintain localized interactions, generate electro-chemical gradients, and help in selecting cooperative functions as they arise. These functions pave the way for the emergence and maintenance of simple metaboli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 69 publications
0
7
0
Order By: Relevance
“…In GARD, the rate of amphiphilic monomer incorporation is dictated kinetically by the current assembly composition (figure 1). Such a dependency is analogous to that invoked by Nowak [68] for prebiotic selection involving templatefree elongation of polymers within compartments. In Nowak's model, there is influence of sequence motifs on the rate of incorporation of new monomers into growing polymers.…”
Section: Compositional Homeostasismentioning
confidence: 63%
See 1 more Smart Citation
“…In GARD, the rate of amphiphilic monomer incorporation is dictated kinetically by the current assembly composition (figure 1). Such a dependency is analogous to that invoked by Nowak [68] for prebiotic selection involving templatefree elongation of polymers within compartments. In Nowak's model, there is influence of sequence motifs on the rate of incorporation of new monomers into growing polymers.…”
Section: Compositional Homeostasismentioning
confidence: 63%
“…We plan to rely on standard biological scrutiny modes, exemplified by metabolic flux analyses that depict how unicellular organism grows homeostatically upon absorbing specific food compounds [ 212 ]. An appropriate compromise will be kept between attributes that are entered ad hoc and those that constitute emergent phenomena, as exemplified [ 68 ].…”
Section: Metabolism Firstmentioning
confidence: 99%
“…This problem highlights the necessity of a physical structure akin to a “warm little pond” for concentrating primary mutualists [84]. Without physical structure, such as a vesicle or a membrane, to contain mutualists, or a physical substrate providing a common ecological niche, it would be hard for the population to aggregate sufficiently to kick-start necessary mutualistic reactions [85,86]. This underscores the importance of conducive ecology, a spatial structure offering just the right amount of flux, enough to concentrate hypercycle components so as to initiate amplification of the cycle [49].…”
Section: Integrated Modellingmentioning
confidence: 99%
“…13,14 One physical realization of these models can be envisioned as rocky surfaces potentially undergoing wet-dry cycles. 13,15,23,24 Group selection research, studied in abstract and also in the context of protocells, suggested that compartments provide necessary functionalities like collocalization of members for reactions, 5,6,25,26 creation of gradients across boundaries (e.g. in lipid membranes 27 ), exclusion of parasites through division 11,19,20 and rise of diversity through merging, 28 all provide benefits for cooperators.…”
Section: Introductionmentioning
confidence: 99%